2019
DOI: 10.1037/pne0000142
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the self-reference effect in younger and older adults.

Abstract: Relating information to the self improves memory. However, this self-reference effect (SRE) is typically studied through explicit self-judgments on individual trials. The current study assessed whether a self-referential mode of thought, induced through a writing task, also induced an SRE on a later task. The study also tested the effects of aging on the SRE, given that a long-lasting mnemonic strategy may be especially relevant for this group. Ninety-two younger adults and 60 older adults were assigned to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 86 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…Previous research has observed a reduction of the SRE by reflecting on autobiographical memories (Jackson et al, 2019). Studies from social psychology have proposed that people tend to distance themselves from their past and regard it as "another person" due to personal changes across the lifespan, adopting a third-person perspective when recalling past behaviors or traits that differ with their current self-concept (Libby & Eibach, 2002;Proning & Ross, 2006).…”
Section: The Temporal Perspective In Selfidentity: the Present Studymentioning
confidence: 99%
“…Previous research has observed a reduction of the SRE by reflecting on autobiographical memories (Jackson et al, 2019). Studies from social psychology have proposed that people tend to distance themselves from their past and regard it as "another person" due to personal changes across the lifespan, adopting a third-person perspective when recalling past behaviors or traits that differ with their current self-concept (Libby & Eibach, 2002;Proning & Ross, 2006).…”
Section: The Temporal Perspective In Selfidentity: the Present Studymentioning
confidence: 99%
“…Specifically, it may be that devising practice tests that provide fewer retrieval cues (i.e., lower constraint testing conditions) during practice tests might lead to higher retention of course materials. Understanding how different varieties of encoding or study strategies influence memory is an important area of research (Colton et al., 2013 ; Dunlosky & Hertzog, 2000 ; Finley & Benjamin, 2012 ; Hertzog et al., 2008 ; Jackson et al., 2019 ; Leshikar & Duarte, 2012 , 2014 ; Leshikar et al., 2010 ; Leshikar, Dulas, et al., 2015 ; Meyer et al., 2020 ; Naveh‐Benjamin et al., 2007 ; Tullis et al., 2013 ; Wong et al., 2017 ), and the present investigation adds to the literature on techniques to improve memory for studied materials.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant because in the current investigation, participants were making predictions about targets that did not involve the self, which may have made the prediction task lower in self salience. Thus, future work might deploy procedures that enhance the self‐salience of the prediction task, such as those used in investigating memory for self‐relevant information (i.e., self‐reference effects; Brown et al., 1986 ; Burden et al., 2021 ; Gutchess et al., 2007 ; Ilenikhena et al., 2021 ; Jackson et al., 2018 ; Leshikar & Duarte, 2012 , 2014 ; Leshikar & Gutchess, 2015 ; Leshikar et al., 2015 ; Leshikar et al., 2016 , 2017 ; Rogers et al., 1977 ; Symons & Johnson, 1997 ; Wong et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%